2011
DOI: 10.15373/2249555x/apr2014/196
|View full text |Cite
|
Sign up to set email alerts
|

Case control study of ABO blood group and Rhesus (Rh) factor in type 2 Diabetes Mellitus

Abstract: Our aim was to determine the association of diabetes mellitus with ABO and Rhesus(Rh) blood groups. 100 blood samples were taken(50 healthy controls and 50 diabetic patients) and analysed for blood sugar(GODPOD method) and blood group(using standard antisera). Patients having fasting blood sugar>126mg/dl were considered diabetic. Statistical analysis was done using chi-square test. Frequency of blood group B was high in both patients(46%) and controls(44%). The order of distribution in both groups were similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…Nevertheless, the frequency of blood group B was slightly higher among T2DM patients compared to the high frequency of nondiabetic patients with blood group O. A similar pattern of results was found by Shrestha et al (2014), whereby no association was found between the ABO blood group and T2DM, and blood group B appearing as the most frequent among diabetic patients (12). Mandal et al…”
Section: Discussionsupporting
confidence: 74%
“…Nevertheless, the frequency of blood group B was slightly higher among T2DM patients compared to the high frequency of nondiabetic patients with blood group O. A similar pattern of results was found by Shrestha et al (2014), whereby no association was found between the ABO blood group and T2DM, and blood group B appearing as the most frequent among diabetic patients (12). Mandal et al…”
Section: Discussionsupporting
confidence: 74%